Pour une théorie de l’éditorialisation - Marcello Vitali-Rosati (Humanités Numériques)
The “digital turn” has been the object of many disciplinary interpretations: from media studies to the information and communication sciences, sociology, psychology, political sciences, and so on. This is not surprising if one considers –with Milad Doueihi– that the “digital turn” can be conceived as a cultural phenomenon, affecting all aspects of our lives and calling into question all our conceptual categories.The term “digital humanities” can somehow serve to signify this universality of the digital turn: it adresses the question of what humanity becomes in the digital age. Philosophy tries to take into account the same universality: beyond any disciplinary specificity, the philosophical questioning aims to understand a phenomenon or a fact in all its implications.This paper starts from the concept of editorialisation to propose a philosophical theory of the world in the digital age. A philosophy therefore not “of the digital turn”, because the object of philosophy can only be universal, but rather a philosophy “in the digital age”.